Agronomic and qualitative performance of some special grain bean cultivars - Cavalcante, Adailza Guilherme [UNESP]; Lemos, Leandro Borges [UNESP]; Meirelles, Flávia Constantino [UNESP]; Filla, Vinicius Augusto [UNESP]; Cavalcante, Alian Cássio Pereira; de Aquino, Leonardo Angelo (Southern Cross Publishing, 2021)
In Brazil, bean consumption is predominated by grains like carioca, but special grains are gaining space on Brazilian tables and can be a source of income for producers. The objective of this study was to evaluate the agronomic and qualitative performance of common bean cultivars with special grains, aiming to identify those with productive potential and superior technological characteristics. The treatments consisted of nine bean cultivars with special grains: BRS Radiante, BRS Realce, BRS Pitanga, BRSMG Tesouro, BRS Marfim, BRSMG União, IAC Tigre, EPAMIG Ouro Vermelho, and EPAMIG Ouro da Mata. The agronomic (number of pods per plant, number of grains per pod, mass of 100 grains, and grain yield) and qualitative (sieve yield, crude protein, cooking time, percentage of imbibition before and after cooking, percentage of whole grains after cooking, and grain hydration capacity) attributes were evaluated. There were statistical differences between cultivars for the number of grains per pod and mass of 100 grains. The cultivars EPAMIG Ouro Vermelho, BRS Marfim, and BRS Pitanga presented the highest yields, with values of 2,907, 2,871, and 2,608 kg ha-1, respectively. There was variability between cultivars for all qualitative attributes. The cultivars BRS Radiante, BRSMG Realce, BRSMG Tesouro, IAC Tigre, and EPAMIG Ouro Vermelho stood out with superior quality grains
Keywords: Phaseolus vulgaris L.; production component; productivity; technological characteristics of grains